2021
DOI: 10.1161/circulationaha.120.052899
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Pathway Limitations in Patients With Chronic Thromboembolic Pulmonary Hypertension

Abstract: Background: Exertional intolerance is a limiting and often crippling symptom in patients with chronic thromboembolic pulmonary hypertension (CTEPH). Traditionally the etiology has been attributed to central factors, including ventilation-perfusion mismatch, increased pulmonary vascular resistance and right heart dysfunction and uncoupling. Pulmonary endarterectomy and, balloon pulmonary angioplasty provide substantial improvement of functional status and hemodynamics. However, despite normalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
(69 reference statements)
2
18
1
Order By: Relevance
“…Previous studies showed that concomitant microvasculopathy had a strong influence on the outcome of PEA ( 2 , 21 ). Moreover, microvasculopathy is irreversible, and patients with advanced microvascular impairment can still suffer from exercise intolerance and hypoxia even after normalization of pulmonary hemodynamics by PEA or BPA ( 22 , 23 ). In the present study, the DLCO was comparable between the baseline and follow-up, which was consistent with previous studies ( 24 , 25 ) and suggested a limited effect of BPA on microvasculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that concomitant microvasculopathy had a strong influence on the outcome of PEA ( 2 , 21 ). Moreover, microvasculopathy is irreversible, and patients with advanced microvascular impairment can still suffer from exercise intolerance and hypoxia even after normalization of pulmonary hemodynamics by PEA or BPA ( 22 , 23 ). In the present study, the DLCO was comparable between the baseline and follow-up, which was consistent with previous studies ( 24 , 25 ) and suggested a limited effect of BPA on microvasculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Combining CPET with right heart catheterization or cardiac imaging may uncover exercise pulmonary hypertension, uncoupling of the right heart from the pulmonary circulation or altered matching of convective and diffusive O 2 transport mechanisms [ 29 ]. Such analyses were recently reported in patients with chronic thromboembolic pulmonary hypertension [ 30 ] or heart failure [ 31 ]. There is an intriguing tendency to exercise hyperventilation in long COVID [ 13 , 14 ], which may relate to persistent lung thrombotic or fibrotic changes, anemia, hypoxemia or altered chemosensitivity.…”
mentioning
confidence: 89%
“…The third study by Motiejunaite et al reports on 114 patients evaluated 3 months after hospital discharge [ 14 ]. Median values of VO 2 max, maximum O 2 pulse and V E /VCO 2 slope were respectively at 18 (IQ 15–21) mL·kg·min −1 , 10 [ 8 – 12 ] mL and 33 [ 30 – 33 , 34–38]. The authors insisted on the contribution of increased V E /VCO 2 , which was higher than the upper limit of normal of 35 in one fourth of the patients, to exercise dyspnea, but otherwise confirmed a deconditioning CPET profile with lower VO 2 max than in other studies tentatively explained by comorbidities and more severe initial disease.…”
mentioning
confidence: 99%
“…Previous pathological studies have reported frequent presentation of the thickened alveolar wall and deficient angiogenesis in the lungs of CTEPH patients ( 28 ), suggesting that the abnormalities of both the alveolar membrane and pulmonary capillary might contribute to the decrease of DLCO in CTEPH. Howden et al have reported a decrease in oxygen delivery in CTEPH patients at peak exercise ( 15 ), and the mean oxygen delivery at rest was < 645 ml/min in CTEPH patients in our study, which we think was below the normal level, and the reasons for which were as follows: (i) The oxygen delivery is determined by cardiac output and arterial oxygen content, which could be affected by any pathophysiology with an impact on these indices ( 19 ); (ii) The arterial oxygen content is a parameter derived from SaO 2 and PaO 2 ( 19 ); and (iii) The cardiac output index (< 1.9 L/min/m 2 ), SaO 2 (< 93%), and PaO 2 (< 67 mmHg) in CTEPH patients were all below normal levels in this study. The oxygen extraction of patients with CTEPH in our study was less than 180 ml/min (reference value for adults: 250 ml/min) ( 29 ), indicating a secondary impairment of oxygen use in the periphery in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CTEPH, occlusion of the pulmonary artery can reduce lung perfusion, causing mismatched ventilation/perfusion and an abnormality in lung function, particularly a decreased lung diffusion capacity ( 13 , 14 ). Moreover, a recent seminal study found that in addition to the pulmonary gas exchange, multiple steps of the oxygen pathway were defective in patients with CTEPH, including oxygen extraction by peripheral tissues, and pulmonary vascular interventions could partly correct the impaired oxygen pathway ( 15 ), in which only 10 patients had available data on the oxygen pathway after intervention. Despite the improved outcomes of CTEPH patients treated with PEA and BPA, the effects of these two interventions on the oxygen pathway are not well demonstrated and have not yet been compared.…”
Section: Introductionmentioning
confidence: 99%